Walking on eggshells: disabled people's management of emotions during everyday encounters in accessible parking spaces - Kubenz, Vera Isabella (Frontiers in Sociology, 2025)
This paper explores how disabled people manage their own and other's emotions during encounters with strangers in accessible parking spaces in a UK context. Due to their mundanity, the affective impact of encounters is frequently not considered in the move towards removing barriers to public space for disabled people. Understanding the energy and emotion work that goes into managing these affects therefore offers a crucial new perspective on how we understand what “accessibility” means. Situating my analysis at the intersection between the sociology of emotions and critical disability studies, I present data from 20 disabled interview participants in England on their experiences of accessible parking encounters. This includes a discussion of the impression management and emotion work required to navigate encounters in parking spaces, and the exclusionary impact these encounters can have over time. In the findings I highlight how considering relational and psycho-emotional aspects of disablism are crucial when understanding everyday oppression and offer a way to rethink the negative emotions arising from encounters as a collective rather than an individual experience.